2014
DOI: 10.1186/2049-6958-9-31
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis and coronary artery disease

Abstract: Idiopathic pulmonary fibrosis (IPF) is defined as a chronic fibrosing interstitial disease of unknown cause, limited to the lungs, and associated with the histopathologic and/or radiologic pattern of usual interstitial pneumonia (UIP); it generally progresses into respiratory failure and death. Although progression of the disease is the most common cause of death, there are increasing reports of its association with other pathologies has been reported: e.g., IPF patients seem more susceptible to cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Guidelines currently recommend pulmonary rehabilitation for most IPF patients, although it is highlighted how programmes need to be tailored [93]. CPET therefore represents a crucial element for better selecting patients, designing personalised training and rehabilitation protocols and more accurate evaluating outcomes of response [85,94,95].…”
Section: Exercise Training and Pulmonary Rehabilitation In Ildmentioning
confidence: 99%
“…Guidelines currently recommend pulmonary rehabilitation for most IPF patients, although it is highlighted how programmes need to be tailored [93]. CPET therefore represents a crucial element for better selecting patients, designing personalised training and rehabilitation protocols and more accurate evaluating outcomes of response [85,94,95].…”
Section: Exercise Training and Pulmonary Rehabilitation In Ildmentioning
confidence: 99%
“…It also provides insight into whether or not these patients are a candidate for a lung transplant. 25 Nathan et al have demonstrated the utility of CTA to look for coronary calcifications to predict further cardiac workup requirements in patients with IPF. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that fibrotic lung disorders predispose to coronary artery disease (CAD) (9,10). To the best of our knowledge, in the literature, we did not identify a study in which subclinical atherosclerosis was detail evaluated by cardiovascular risk tests in IPF patients.…”
Section: Introductionmentioning
confidence: 91%